Influence of exogenous salicylic acid on antioxidant enzyme activities in the roots of salt stressed tomato plants - Szepesi, Ágnes (Acta Biologica Szegediensis, 2008)
Up-regulation of the antioxidant system provides protection against NaCl-induced oxidative damage in plants. Activities of antioxidant enzymes and hydrogen peroxide (H2O2) levels in the roots of tomato (Lycopersicon esculentum Mill. L.) plants were investigated to assess the antioxidant protection offered by long-term (3 weeks) exogenous salicylic acid (SA)pre-treatment against 100 mM NaCl induced salt stress. Our results suggest that 10-4 M SA was effective in increasing the activities of enzymes involved in the antioxidant system.